Florida Citrus Rootstock Selection Guide, 3rd Edition - William S. Castle; Kim D. Bowman; Jude W. Grosser; Stephen H. Futch; James H. Graham (EDIS)
Information about citrus rootstocks has become an important part of understanding and managing citrus greening (Huanglongbing or HLB). This selection guide covers 20 characteristics of 45 citrus rootstocks and explains its methodology in detail. This revised 3-page fact sheet was written by William S. Castle, Kim D. Bowman, Jude W. Grosser, Stephen H. Futch, and James H. Graham and published by the UF Department of Horticultural Sciences, May 2015.